2006
DOI: 10.1194/jlr.p600002-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial lipase is associated with inflammation in humans

Abstract: The aim of this study was to investigate the extent to which inflammation is linked with plasma endothelial lipase (EL) concentrations among healthy sedentary men. Plasma C-reactive protein (CRP) concentrations were measured with a highly sensitive commercial immunoassay, plasma interleukin-6 (IL-6) concentrations were measured using a commercial ELISA, and plasma secretory phospholipase A 2 type IIA (sPLA 2 -IIA) concentrations were measured using a commercial assay in a sample of 74 moderately obese men (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 30 publications
1
52
3
2
Order By: Relevance
“…It has been reported that EL expression is highly regulated by a variety of factors including inflammatory cytokines, biomechanical forces, lipopolysaccharide, angiotensin II, and oxidized LDL (29 -31 ). In fact, plasma EL mass was increased in experimental endotoxemia in humans and correlated with inflammatory markers such as C-reactive protein, interleukin-6, and secretory phospholipase A2-IIa (32,33 ). In contrast, statins reduce EL expression and plasma EL mass (16,34 ), which is accompanied by increased plasma HDL-C concentrations in humans (16 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that EL expression is highly regulated by a variety of factors including inflammatory cytokines, biomechanical forces, lipopolysaccharide, angiotensin II, and oxidized LDL (29 -31 ). In fact, plasma EL mass was increased in experimental endotoxemia in humans and correlated with inflammatory markers such as C-reactive protein, interleukin-6, and secretory phospholipase A2-IIa (32,33 ). In contrast, statins reduce EL expression and plasma EL mass (16,34 ), which is accompanied by increased plasma HDL-C concentrations in humans (16 ).…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio se observó una correlación positiva entre la cantidad de grasa visceral y los niveles de LE, probablemente, secundario a otras alteraciones metabólicas asociadas a esta condición 48 . Finalmente, se ha demostrado que en humanos existe una correlación directa entre marcadores proinfl amatorios (PCRus, IL-6, entre otros) y concentraciones plasmáticas de LE, lo que apoya la hipótesis de que la enzima se encuentra sobre regulada en condiciones de infl amación 49,50 .…”
Section: Papel De Le En Distintas Patologías: Enfásis En Enfermedad Cunclassified
“…These studies suggest both pro-and antiatherogenic properties of HL, and indicate complex, contextdependent involvement of HL in cardiovascular disease [13]. EL is also emerging as an important factor in the control of lipoprotein metabolism and inflammation in humans [23,24,[68][69][70]. EL has recently been identified as an important determinant of plasma HDL-C levels [40][41][42][43], reflecting its primary role in HDL catabolism.…”
Section: Lipases In Diseasementioning
confidence: 99%
“…In addition, HL and EL have important roles in HDL remodeling and uptake that are essential to the process of reverse cholesterol transport [11,14]. Indeed, all the lipases emerge as important genetic determinants of circulating lipid levels in human populations and are thought to contribute to a number of pathogenic states including atherosclerosis and inflammation, obesity and insulin secretion and sensitivity (discussed later) [11,[21][22][23][24][25][26][27]. However, regardless of the role, lipases can function only when secreted, a process that first requires their maturation in the endoplasmic reticulum (ER).…”
mentioning
confidence: 99%